Establishing the Intimate Link: 20th Century Tropical Agriculture and the Establishment of the Coconut Zone - Philip Jan Cerepak (Diponegoro University, 2020)
This paper examines the role of colonial science institutions in imagining and developing the Coconut Zone, an area of intense coconut production that extends from the small Pacific island chains encompassing the Caroline and the Marshall Islands, all the way to northern Papua, the Philippines, Indonesia, Malaysia, Sri Lanka, and Southern India. Through an examination of European colonial science institutions, as well as the Philippine Bureau of Science, and Agriculture, this paper establishes the intimate connection between western consumers and tropical producers. Here, within the agricultural institutions, we are able to see the burgeoning demand for copra production and a formation of a distinct Coconut Zone. This paper builds upon Sydney Mintz’s theoretical articulation of sugar production to situate copra, the dried meat of the coconut, in conversation with other global, colonial commodities.